A new strong pearlitic multi-principal element alloy to withstand wear at elevated temperatures. (1st April 2022) - An, X.L.; Liu, Z.D.; Zhang, L.T.; Zou, Y.; Xu, X.J.; Chu, C.L.; Wei, W.; Sun, W.W.
Abstract: Alloys with high wear resistance at elevated temperatures are highly desired for modern application under extreme working conditions. Conventionally, nano-layered pearlitic structure could greatly improve the strength and wear resistance for steels, but they are not heat resistant. Therefore, it is promising to make a new pearlite structure that could withstand heat. In this study, we revitalize the pearlite structure by inheriting it from single principal element iron alloys into a newly developed multi-principal element alloy (MPEA) through a classic eutectoid reaction, producing a nanometre sized layered microstructure. Taking advantages of the thermal stability of MPEAs, formation of strong pearlite not only significantly improves the room temperature wear resistance of the MPEA, more importantly, it endues the MPEA with excellent elevated temperature strength and wear resistance. Therefore, pearlitic structure is a direction worthy of pursuing in microstructural design of high performance MPEAs. Graphical abstract: Image, graphical abstract